PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM LITERASI BELAJAR ERA PANDEMI COVID – 19 DI DESA SUMBERKOLAK KECAMATAN PANARUKAN (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Covid – 19 has had an impact on various sectors, one of which is the education sector. Online learning or distance learning is a must. Online learning is felt by all levels of education. The teacher gives school assignments through online learning support applications or whatsappgroups. This is felt by children and parents in Sumberkolak Village, Panarukan District, Situbondo Regency. Resulting in dependence on using gadgets and reducing interest in reading. And other general knowledge. Parents feel overwhelmed in guiding their sons and daughters in doing schoolwork. They also have free time which is not accompanied by productive activities. Back to Village Community Service Program as an effort to empower the community organized by UNEJ is oriented towards optimizing children's literacy. The activity focuses on literacy and learning activists for elementary school children. This activity uses the Participatory Action Research (PAR) method. The result of this activity is the creation of a conducive and comfortable atmosphere in literacy and learning activities, as well as stimulating children's creativity and skills during the pandemic. Forming children who are active, confident, caring, and independent. Keywords: Online Learning, Literacy, Community Empowerment